(untitled) - Dr. Harith Kadhim HASAN (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The Iraqi learner of French as a foreign language has one or more language systems. The interference of knowledge of these previous systems, particularly Arabic for our study, poses a problem in learning French as a foreign language. This paper aims to identify the types of interference that Arabic exerts on French among Iraqi students who learn French as a foreign language and explain the sources of these errors. We will not offer solutions for this interference, but we suggest measures to prevent it and reduce frequent interference.